A generic framework for symbolic execution: A coinductive approach. (May 2017) - Lucanu, Dorel; Rusu, Vlad; Arusoaie, Andrei
Abstract: We propose a language-independent symbolic execution framework. The approach is parameterised by a language definition, which consists of a signature for the syntax and execution infrastructure of the language, a model interpreting the signature, and rewrite rules for the language's operational semantics. Then, symbolic execution amounts to computing symbolic paths using a derivative operation. We prove that the symbolic execution thus defined has the properties naturally expected from it, meaning that the feasible symbolic executions of a program and the concrete executions of the same program mutually simulate each other. We also show how a coinduction-based extension of symbolic execution can be used for the deductive verification of programs. We show how the proposed symbolic-execution approach, and the coinductive verification technique based on it, can be seamlessly implemented in language definition frameworks based on rewriting such as the K framework. A prototype implementation of our approach has been developed in K . We illustrate it on the symbolic analysis and deductive verification of nontrivial programs.